Critical Discourse Analysis of Technology-Based Village Government System in Bengkalis Riau - Rijalul Fikri; Muhammad Faisal Amrillah; Budi Mulianto (Journal of Local Government Issues (LOGOS), 2020)
This study aims to comprehend on how the discourse of e-government system in villages of Bengkalis Regency, Riau Province, by using the method of Foucauldian discourse analysis. Thus, discourse of this paper is the implementation of e-governance system forming the relation between power and society through the process of definition, isolation and justification. In the e-government system’s operation in Bengkalis, there are two remarkable interpretation as follows: firstly, for villages that adopted the e-government system, those involve in the interpretation of dominant discourse which define and justify the discourse of e-government system; and secondly, for villages that have still been in loyal of the local wisdom – “committing to the government system and society life order based on traditional, well known as self-governing community” -, those include in the interpretation of the marginalized discourse that means in the wider discursive context it is the discursive implementation of e-government system. As a logical conclusion, the existing discourse has expressed the state power represented by the effort of e-government system’s employment in which there are the major interpretation of village government categorized in the dominant discourse and the marginalized discourse.